2007
DOI: 10.1890/06-0674
|View full text |Cite
|
Sign up to set email alerts
|

Nonadditive Effects of Leaf Litter Species Diversity on Breakdown Dynamics in a Detritus-Based Stream

Abstract: Since species loss is predicted to be nonrandom, it is important to understand the manner in which those species that we anticipate losing interact with other species to affect ecosystem function. We tested whether litter species diversity, measured as richness and composition, affects breakdown dynamics in a detritus-based stream. Using full-factorial analyses of single- and mixed-species leaf packs (15 possible combinations of four dominant litter species; red maple [Acer rubrum], tulip poplar [Liriodendron … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
143
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(161 citation statements)
references
References 79 publications
(100 reference statements)
15
143
0
2
Order By: Relevance
“…However, microbial communities often process mixtures of plant litter substrates (species and genotypes) at rates faster than expected from the average of the decomposition rates of the component litter types decomposing by themselves (Schweitzer et al 2005;LeRoy and Marks 2006;HĂ€ttenschwiler and Gasser 2005;Madritch et al 2006;Jonsson and Wardle 2008), a phenomenon termed a synergistic eVect or synergism [as opposed to an antagonistic eVect, which occurs less frequently (Wardle and Nicholson 1996;Bardgett and Shine 1999;Kominoski et al 2007)]. Despite the relevance of synergistic eVects of litter mixing to questions about biodiversity and ecosystem function and recent calls for more mechanistic studies (Gartner and Cardon 2004;, the mechanisms underlying synergistic decomposition remain elusive.…”
Section: Introductionmentioning
confidence: 99%
“…However, microbial communities often process mixtures of plant litter substrates (species and genotypes) at rates faster than expected from the average of the decomposition rates of the component litter types decomposing by themselves (Schweitzer et al 2005;LeRoy and Marks 2006;HĂ€ttenschwiler and Gasser 2005;Madritch et al 2006;Jonsson and Wardle 2008), a phenomenon termed a synergistic eVect or synergism [as opposed to an antagonistic eVect, which occurs less frequently (Wardle and Nicholson 1996;Bardgett and Shine 1999;Kominoski et al 2007)]. Despite the relevance of synergistic eVects of litter mixing to questions about biodiversity and ecosystem function and recent calls for more mechanistic studies (Gartner and Cardon 2004;, the mechanisms underlying synergistic decomposition remain elusive.…”
Section: Introductionmentioning
confidence: 99%
“…One consequence is the loss of a specific leaf species from the detrital pool. Given there can exist substantial interspecific variation in litter resource quality (Ostrofsky 1997, Swan et al 2009), loss of leaf species diversity on organic matter processing is being increasingly studied (e.g., Kominoski et al 2007, Lecerf et al 2007, 2011, Schindler and Gessner 2009, Swan et al 2009). To date, there has been no explicit test of what the implications of litter species loss are for stability of ecosystem processing of detritus, nor the potential mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of P. gentilis was manipulated in a full factorial design with 11 leaf litter treatments (6 single-species, 4 five-species mixtures, and a mixture of all six species; Table 1). Diversity was reduced by removing in four mixture treatments each of the dominant overstory species as they each represent targets of realistic losses to forest communities (e.g., logging, invasive pests) and can overwhelmingly contribute to changes in breakdown dynamics (Kominoski et al 2007, Swan et al 2009, Lecerf et al 2011. A cage design was employed whereby a fixed mass of leaf litter was enclosed in a plastic cage with or without four individual P. gentilis larvae and allowed to break down for 39-40 days.…”
Section: Experimental Manipulation Of Consumer Presence and Litter DImentioning
confidence: 99%
“…Empirical evidence for facilitation or inhibition of breakdown of species in mixtures is conflicting. Some studies have shown non-additive effects (McArthur et al 1994;Swan and Palmer 2004;Kominoski et al 2007), whereas others have not (Leff and McArthur 1989;Lecerf et al 2007). Taylor et al (2007) showed that the initial foliar chemistry strongly influenced whether breakdown rates were nonadditive.…”
Section: Mixed-species Versus Single-species Packsmentioning
confidence: 99%
“…where mixtures of different leaf species facilitate or inhibit breakdown of one or more species in the mixture). Some studies have shown that breakdown rates in mixtures are non-additive (McArthur et al 1994;Swan and Palmer 2004;Kominoski et al 2007), while others have shown limited or no evidence of non-additive effects (Leff and McArthur 1989;Lecerf et al 2007;Taylor et al 2007). It is not known, however, whether disturbances like acidic deposition augment or reduce non-additive effects.…”
Section: Introductionmentioning
confidence: 99%